2009
DOI: 10.1007/s10562-009-0177-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La2O3 on Ru/CeO2-La2O3 Catalyst for Ammonia Synthesis

Abstract: A series of CeO 2 -La 2 O 3 supported ruthenium catalysts were prepared by co-precipitation method and the as-obtained samples were characterized by N 2 physisorption, X-ray diffraction, CO chemisorption, H 2 -TPR, H 2 -TPD and XPS. The activity test shows that ammonia concentration of the catalyst with 10% La is 13.9% at 10 MPa, 10,000 h -1 , 450°C, which is 17% higher than that of Ru/CeO 2 . La doping can improve the activity of Ru-ceria catalyst for ammonia synthesis by facilitating the reduction of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 34 publications
(45 reference statements)
2
20
0
1
Order By: Relevance
“…The mesoporous character of the materials is confirmed by BET, as seen in the typical type IV isotherms with H2 hysteresis shown in Figure 2 (top, a and b). The surface area of the lanthana is close to 60 100 m 2 /g after calcination at 450 °C (see Table 1), well in excess of previously reported surface areas of less than 30 m 2 /g 30,31 . XRD shows that the sample is largely amorphous after calcination at 450 °C (Figure 2 (Table 1), which can be attributed to the small particle size attributed to agglomerates of spheres with roughly uniform size, resulting in narrow pore size distributions 34 .…”
Section: Pure Oxidessupporting
confidence: 82%
“…The mesoporous character of the materials is confirmed by BET, as seen in the typical type IV isotherms with H2 hysteresis shown in Figure 2 (top, a and b). The surface area of the lanthana is close to 60 100 m 2 /g after calcination at 450 °C (see Table 1), well in excess of previously reported surface areas of less than 30 m 2 /g 30,31 . XRD shows that the sample is largely amorphous after calcination at 450 °C (Figure 2 (Table 1), which can be attributed to the small particle size attributed to agglomerates of spheres with roughly uniform size, resulting in narrow pore size distributions 34 .…”
Section: Pure Oxidessupporting
confidence: 82%
“…Luo et al [58] also studied the reduction of Ce(La)O x solid solutions and found that the reduction of surface capping oxygen of ceria is located at intervals of 250-400 • C and the bulk oxygen of ceria is located at 450-700 • C. Similar findings were reported by Li et al [28] for Ni/CeO 2 -La 2 O 3 and Cu/CeO 2 -La 2 O 3 catalysts. The difference in the reduction temperature of these supports in comparison with the support of the present paper may be related to the preparation method.…”
Section: Characterizationsupporting
confidence: 69%
“…3a shows the TPR profile of the CeO 2 , Ce 4 La, Ce 8 La and Ce 12 La supports, where it can be observed that the reduction peak located at 550 • C in CeO 2 (peak related to surface-capping oxygen of CeO 2 ) is shifted to lower temperature, after addition of La 2 O 3 . This finding suggests that this displacement is due to the solid solution Ce(La)O x formed [58,61,28].…”
Section: Characterizationmentioning
confidence: 89%
See 2 more Smart Citations